A proposal for a standard interface between Monte Carlo tools and one-loop programs - Binoth, Thomas; Boudjema, F.; Dissertori, G.; Lazopoulos, A.; Denner, A.; Dittmaier, S.; Frederix, R.; Greiner, N.; Höche, S.; Giele, W.; Skands, P.; Winter, J.; et al. (Computer physics communications, 2010)
Many highly developed Monte Carlo tools for the evaluation of cross sections based on tree matrix elements exist and are used by experimental collaborations in high energy physics. As the evaluation of one-loop matrix elements has recently been undergoing enormous progress, the combination of one-loop matrix elements with existing Monte Carlo tools is on the horizon. This would lead to phenomenological predictions at the next-to-leading order level. This note summarises the discussion of the next-to-leading order multi-leg (NLM) working group on this issue which has been taking place during the workshop on Physics at TeV Colliders at Les Houches, France, in June 2009. The result is a proposal for a standard interface between Monte Carlo tools and one-loop matrix element programs. Dedicated to the memory of, and in tribute to, Thomas Binoth, who led the effort to develop this proposal for Les Houches 2009. Thomas led the discussions, set up the subgroups, collected the contributions, and wrote and edited this paper. He made a promise that the paper would be on the arXiv the first week of January, and we are faithfully fulfilling his promise. In his honour, we would like to call this the Binoth Les Houches Accord.
Gesehen am 03.02.2023